exoALMA. XIV. Gas Surface Densities in the RX J1604.3−2130 A Disk from Pressure-broadened CO Line Wings - Tomohiro C. Yoshida; Pietro Curone; Jochen Stadler; Stefano Facchini; Richard Teague; Munetake Momose; Sean M. Andrews; Jaehan Bae; Marcelo Barraza-Alfaro; Myriam Benisty; Gianni Cataldi; Daniele Fasano; et al. (The Astrophysical Journal Letters)
Gas surface density is one of the most relevant physical quantities in protoplanetary disks. However, its precise measurement remains highly challenging due to the lack of a direct tracer. In this study, we report the spatially resolved detection of pressure-broadened line wings in the CO J  = 3–2 line in the RX J1604.3−2130 A transition disk as part of the exoALMA large program. Since pressure-broadened line wings are sensitive to the total gas volume density, we robustly constrain the radial dependence of the gas surface density and midplane pressure in the region located 50–110 au from the central star, which encompasses the dust ring of the system. The peak radius of the midplane pressure profile matches the dust ring radial location, directly proving radial dust trapping at a gas pressure maximum. The peak gas surface density is 18–44 g cm ^−2 and decreases at radii interior to and exterior of the dust ring. A comparison of the gas and dust surface densities suggests that the disk turbulence is as low as α _turb  ∼ 2 × 10 ^−4 . Despite dust trapping, the gas-to-dust surface density ratio at the ring peak is 70–400, which implies already-formed protoplanets and/or less efficient dust trapping. The gas surface density drop at radii interior to the ring is consistent with a gas gap induced by a Jupiter-mass planet. The total gas mass within 50 <  r  < 110 au is estimated to be ∼0.05–0.1 M _⊙ (50–100 M _Jup ), suggesting that planetary system formation is possible.